The Influence of the Implementation of Public Sector Accounting Models in Fraud Prevention Efforts in the Digital Era - Nur, Hamzah Fansyuri; Haliah, Haliah; Kusumawati, Andi (Formosa Journal of Science and Technology, 2024)
This research aims to find and describe the characteristics of fraud that occurs in the public sector in the digital era to prevent fraud that occurs in the public sector. The research conducted is literature research sourced from articles that are in accordance with the research topic for further analysis. The results of the study show that the characteristics of fraud in the public sector that occur in the digital era include the use of misconceptions about the role of digital technology in the implementation of public accountant duties. The influence of the implementation of public sector accounting can prevent fraud in the public sector in the digital era if implemented by considering several factors that affect fraud, such as performance accountability, and implementing technical strategies, dual-paradigm approaches, and preventive strategies.